Assessing the population‐level conservation effects of marine protected areas. Issue 6 (30th June 2021) - Ovando, Daniel; Caselle, Jennifer E.; Costello, Christopher; Deschenes, Olivier; Gaines, Steven D.; Hilborn, Ray; Liu, Owen
Abstract: Marine protected areas (MPAs) cover 3–7% of the world's ocean, and international organizations call for 30% coverage by 2030. Although numerous studies show that MPAs produce conservation benefits inside their borders, many MPAs are also justified on the grounds that they confer conservation benefits to the connected populations that span beyond their borders. A network of MPAs covering roughly 20% of the Channel Islands National Marine Sanctuary was established in 2003, with a goal of providing regional conservation and fishery benefits. We used a spatially explicit bioeconomic simulation model and a Bayesian difference‐in‐difference regression to examine the conditions under which MPAs can provide population‐level conservation benefits inside and outside their borders and to assess evidence of those benefits in the Channel Islands. As of 2017, we estimated that biomass densities of targeted fin‐fish had a median value 81% higher (90% credible interval: 23–148) inside the Channel Island MPAs than outside. However, we found no clear effect of these MPAs on mean total biomass densities at the population level: estimated median effect was –7% (90% credible interval: –31 to 23) from 2015 to 2017. Our simulation model showed that effect sizes of MPAs of <30% were likely to be difficult to detect (even when they were present); smaller effect sizes (which are likely to be common) were even harder to detect. Clearly, communicating expectations and uncertainties around MPAs is critical to ensuring that MPAs are effective. We provide a novel assessment of the population‐level effects of a large MPA network across many different species of targeted fin‐fish, and our results offer guidance for communities charged with monitoring and adapting MPAs. Abstract : Article impact statement : Population‐level conservation effects of marine protected areas are likely to be extremely challenging to measure and detect. Resumen: Las áreas marinas protegidas (AMPs) cubren entre 3–7% de los océanos del planeta y las organizaciones internacionales piden una cobertura del 30% para el 2030. Aunque numerosos estudios muestran que las AMPs producen beneficios de conservación dentro de sus límites, muchas de estas áreas también están justificadas por otorgarles beneficios de conservación a las poblaciones conectadas que abarcan más allá de sus fronteras. Una red de AMPs que cubre aproximadamente el 20% del Santuario Marino Nacional de las Islas del Canal fue establecida en 2003 con el objetivo de proporcionar beneficios para la conservación y las pesquerías regionales. Usamos un modelo de simulación bioeconómica espacialmente explícito y una regresión bayesiana de diferencia‐en‐diferencia para examinar las condiciones bajo las que las AMPs pueden proporcionar beneficios de conservación a nivel poblacional dentro y fuera de sus límites y para evaluar las evidencias de esos beneficios en las Islas del Canal. Hasta el 2017, estimamos que la densidad de la biomasa de los peces focalizados tuvo un valor medio de 81% (90% intervalo creíble 23–148) dentro de las AMPs de las Islas del Canal que fuera de ellas. Sin embargo, no encontramos un efecto claro de estas AMPs sobre la densidad de biomasa total promedio a nivel poblacional; el efecto medio estimado fue de ‐7% (90% intervalo creíble ‐31 ‐ 23) entre 2015 y 2017. Nuestro modelo de simulación mostró que los tamaños del efecto de las AMPs menores al 30% tenían mayor probabilidad de ser difíciles de detectar (incluso cuando estaban presentes); los tamaños de efecto más pequeños (que es probable que sean comunes) fueron incluso más difíciles de detectar. Claramente, es muy importante comunicar las expectativas e incertidumbres en torno a las AMPs para asegurar que éstas sean efectivas. Proporcionamos una evaluación novedosa de los efectos a nivel poblacional de una red extensa de AMPs para muchas especies de peces focalizados y nuestros resultados ofrecen una guía para las comunidades encargadas de monitorear y adaptar las AMPs.